Do Foreigners Count? Internationalization of Presidential Campaigns. (March 2017) - Sevin, Efe; Uzunoğlu, Sarphan
The U.S. presidential elections always attract the attention of foreign audiences—who, despite not being able to vote, choose to follow the campaigns closely. For a post that is colloquially dubbed as the "Leader of the Free World, " it is not unexpected to see such an interest coming from nonvoters. Mimicking almost hosting a megaevent, the elections increase the media coverage on the United States, thus making the elections a platform to communicate with the rest of the world and to influence the reputation of the country, or its nation brand. This study postulates that the increasing adoption of social media by campaigns as well as ordinary users, increase the symbolic importance of presidential elections for foreign audiences in two ways. First, foreign audiences no longer passively follow the campaign but rather present their input to sway the American public opinion through social media campaigns. Second, foreign audiences are exposed to a variety of messages ranging from official campaigns to late-night comedy shows to local grassroots movements. The audiences both enjoy a more in-depth understanding of the elections campaigns and are exposed to alternative political views. In this study, the 2016 U.S. presidential elections are positioned as a megaevent that can influence the American nation brand. Through a comparative content and network analyses of messages disseminated over social media in the United Kingdom, Turkey, Canada, and Venezuela, the nation branding–related impacts of election campaigns are investigated.